ANALYSIS OF FACTORS INFLUENCING CUSTOMERS’ INTENTION TO THE ADOPTION OF E-BANKING SERVICE CHANNELS IN BAHIR DAR CITY: AN INTEGRATION OF TAM, TPB AND PR - Takele, Yitbarek; Sira, Zeleke (European Scientific Journal, ESJ, 2013)
This study is undertaken to analyze factors that influence customers’ intention to adopt e-banking service channels in Bahir Dar city. A conceptual framework was developed by integrating six variables from theory of planned behavior, technology acceptance model and previous studies. The findings revealed that attitude, subjective norm, perceived behavioral control, perceived usefulness and perceived ease of use and perceived risk were significant in affecting users’ intention to use e-banking service channels. The construct perceived behavioral control emerged as a dominant factor followed by attitudes and perceived usefulness in predicting an individual’s intention to adopt e-banking service channels. Finally, attitude is jointly predicted by perceived behavioral control, perceived usefulness, perceived ease of use and perceived risk while perceived ease of use contributed more for the variation in attitude.